2001
DOI: 10.1002/jemt.1106
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of CD95, Bcl‐2, and Bax in rat gastric chief and parietal cells

Abstract: Apoptotic cell death is common in the inflamed gastric mucosa, but its role in the regulation of cell homeostasis in normal gastric mucosa is unknown. We investigated the expression of CD95, Bcl-2, and Bax and their roles in the regulation of apoptosis in normal rat gastric mucosa and in cultures of highly enriched rat chief and parietal cells by immunostaining, Western blotting, and FACS. In intact tissue CD95, Bcl-2, and Bax were localized predominantly in the glandular base region in chief cells. In freshly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 37 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…Chief cell cultures made from these highly purified cells were used 2 days after seeding, but it was not mentioned whether they were confluent or not. Additionally, it was demonstrated that cultures made from highly purified chief cells showed a significant reduction in the expression of some proteins found in mature chief cells in vivo (20). Our results show that chief cells in culture must be confluent with a high cell density to, both functionally and structurally, express a phenotype that is similar to chief cells, in vivo.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…Chief cell cultures made from these highly purified cells were used 2 days after seeding, but it was not mentioned whether they were confluent or not. Additionally, it was demonstrated that cultures made from highly purified chief cells showed a significant reduction in the expression of some proteins found in mature chief cells in vivo (20). Our results show that chief cells in culture must be confluent with a high cell density to, both functionally and structurally, express a phenotype that is similar to chief cells, in vivo.…”
Section: Discussionmentioning
confidence: 53%
“…Although this has been accomplished before with chief cells isolated from the dog stomach (2,26,27), such a culture system in rodent species has not been described. In previous studies using chief cells isolated from the rat stomach, cultures were made either by using mixed mucosal cells with no purification (30,31) or by preparing highly purified chief cells (85 Ϯ 11% pure) by elutriation and Percoll density gradient centrifugation (20). Chief cell cultures made from these highly purified cells were used 2 days after seeding, but it was not mentioned whether they were confluent or not.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Apoptosis mediated through the Fas antigen surface receptor pathway plays a central role in Helicobacter-induced gastric mucosal disease in which Fas signaling facilitates parietal and chief cell depletion early in infection (30)(31)(32). Surface Fas antigen expression is markedly up-regulated in the gastric mucosa during infection (33) and is expressed at the highest levels on chief and parietal cell populations.…”
Section: Introductionmentioning
confidence: 99%